Does Routine Posttreatment PET/CT Add Value to the Care of Women With Locally Advanced Cervical Cancer?. Issue 5 (June 2016) - Phippen, Neil T.; Havrilesky, Laura J.; Barnett, Jason C.; Hamilton, Chad A.; Stany, Michael P.; Lowery, William J.
Abstract : Objectives: The aim of this study was to determine the necessary reduction in recurrence rate that would make postchemoradiation positron emission tomography (PET)/computed tomography (CT) to direct completion hysterectomy for locally advanced cervical cancer (LACC) cost-effective. Methods: A decision model evaluated costs and recurrence rates of 2 posttreatment surveillance strategies in LACC: (1) routine surveillance without PET/CT and (2) PET/CT after 3 months to triage to completion hysterectomy. Incremental cost-effectiveness ratios were expressed in dollars per additional cancer recurrence avoided. Model parameters included expected rates of recurrence using each strategy, true- and false-positive rates of posttreatment PET/CT, and major complications of completion hysterectomy. From published data, we modeled an LACC baseline recurrence rate of 32%, PET/CT false-positive rate of 33%, and false-negative rate of 19%. We assumed that PET/CT revealed persistent local cervical cancer in 16% and progressive or distant disease in 6%. Costs of PET/CT, hysterectomy, and treatment for recurrence were based on Medicare reimbursements. A 50% salvage rate with hysterectomy was assumed and varied in sensitivity analysis. Results: Routine use of PET/CT to direct completion hysterectomy was associated with a higher average cost ($16, 579 vs $15, 450) and a lower recurrence rate (26% vs 32%). The incremental cost-effectiveness ratio of PET was $20, 761 per recurrence prevented. When the probability of recurrence after hysterectomy dropped to 25% or less, PET/CT was a dominant strategy. Conclusions: Routine use of PET/CT to determine which patients may benefit from a completion hysterectomy after chemoradiation for LACC has the potential to be highly cost-effective. Abstract : Supplemental digital content is available in the text.